Analisis Pengelolaan Dana Desa untuk Pembangunan Infrastruktur dan Pemberdayaan Masyarakat di Desa Pasir Panjang dan Desa Ciracap - Isep Nazila; Gatot Wahyu Nugroho; Risma Nurmilah (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the management of village funds in infrastructure development and community empowerment in Pasir Panjang and Ciracap Villages, Ciracap District, Sukabumi Regency. The research uses a qualitative approach with data collection techniques including interviews, observations, and documentation. The results show that the management of village funds in both villages has followed the stages of planning, implementation, and reporting in accordance with applicable regulations. However, challenges remain such as limited community participation, lack of human resources, and insufficient transparency in budget reporting. Control efforts are implemented through supervision by the Village Consultative Body (BPD), community participation, and annual accountability reports. Overall, the village fund management has been quite effective in improving basic infrastructure access and supporting economic empowerment, although improvements are needed in transparency and community engagement.